The Recursive Properties of the Error Term of the Fourth Power Mean of the Generalized Cubic Gauss Sums - Zhang Jin; Zhang Jiafan (Journal of Mathematics)
In this paper, we use the analytic methods and the properties of the classical Gauss sums to study the properties of the error term of the fourth power mean of the generalized cubic Gauss sums and give two recurrence formulae for it.